Well-being and satisfaction with life: a quasi-experimental mixed-methods examination of an expressive veteran writing program - Atkinson, Ross M., author; Jennings, Louise, advisor; Doe, Sue, committee member; Most, David, committee member; Schrader, Ben, committee member (Colorado State University. Libraries, 2025)
This quasi-experimental mixed-methods dissertation examines whether participation in a veteran-only expressive writing workshop supports well-being and satisfaction with life. Utilizing a three-manuscript dissertation format, this study integrated quantitative and qualitative approaches over an eight-week intervention and four-week follow-up period, for a total of twelve weeks. Nineteen (n=19) U.S. military veterans were recruited, with thirteen (n=13) completing the study. Six (n=6) attended an eight-week writing workshop, while seven (n=7) formed a control group. Quantitative data were collected using the Satisfaction with Life Scale (SWLS) (Diener et al., 1985) and the Well-Being Inventory (WBI) (Vogt et al., 2018) at four time points in the study. Qualitative data included semi-structured interviews with workshop participants, observations, and participant written stories and reflections. The results indicated that workshop participation led to significantly greater increases in life satisfaction compared to the control, with repeated-measures ANOVA showing a significant time/condition interaction effect (p < .05). Additionally, veteran participants who started with lower baseline satisfaction showed the greatest improvement. While not statistically significant, WBI analyses suggested notable positive changes, particularly in the social domain of well-being for the workshop group. Thematic analysis of the interviews revealed that the workshop provided a safe, camaraderie-rich space for emotional release, identity reconnection, and peer support, further revealing an overlap with the social well-being domain. Participants reported reframing traumatic memories into narratives and experiencing renewed purpose and social connection. Collectively, these findings suggest that expressive writing workshops can be a low-cost and accessible intervention that yields psychological and social benefits for veterans in transition. The study's conclusions have implications for integrating narrative-based peer-writing programs into veteran support services.